A Study to Determine the Association between Monocyte to HDL Cholesterol Ratio, Neutrophil to Lymphocyte Ratio, Red Blood Cell Distribution Width (RDW), and Diabetic Retinopathy in a Tertiary Care Hospital in Eastern India - Rupak Chatterjee; Arindam Naskar; Tania Ray Bhadra; Kingshuk Jana; Shambo Samrat Samajdar; Shatavisa Mukherjee (Bengal Physician Journal)
Background: Diabetic retinopathy is an important microvascular complication of diabetes mellitus (DM) leading to visual impairment. Inflammation of retinal vasculature plays a pivotal role in its pathogenesis. Our aim of this study is to determine the association between diabetic retinopathy and monocyte to high-density lipoprotein (HDL) cholesterol ratio (MHR), neutrophil to lymphocyte ratio (NLR), and red blood cell distribution width (RDW). Methods: One hundred and fifty adult type 2 DM were included based on inclusion and exclusion criteria—50 diabetics without retinopathy, 50 with proliferative retinopathy, and 50 with non-proliferative retinopathy. All patients underwent routine blood investigations and the data was collected and analyzed. Results: The mean NLR, MHR, and RDW were higher in diabetic patients with retinopathy than diabetics without it and it was higher among proliferative diabetic retinopathy than non-proliferative retinopathy subjects. A significant association was found in all cases with a p-value < 0.05. Conclusion: NLR, MHR, and RDW can be useful predicting tools, especially in peripheral setups.